Intramyocardial fate and effect of iron nanoparticles co-injected with MACS® purified stem cell products. (August 2017) - Müller, Paula; Gaebel, Ralf; Lemcke, Heiko; Wiekhorst, Frank; Hausburg, Frauke; Lang, Cajetan; Zarniko, Nicole; Westphal, Bernd; Steinhoff, Gustav; David, Robert
Abstract: Background: Magnetic activated cell sorting (MACS ® ) is routinely used to isolate stem cell subpopulations intended for the treatment of cardiovascular diseases. In strong contrast, studies examining the amount, effect and intramyocardial distribution of iron nanoparticles used for magnetic cell labelling are missing, although iron excess can cause functional disorders in the heart. Methods and results: CD133 + haematopoietic and CD271 + mesenchymal stem cells were purified from bone marrow using automatically and manually MACS ® based systems. Flow cytometric measurements demonstrated a rapid loss of MACS ® MicroBeads from cells under culture conditions, while storage under hypothermic conditions decelerated their detachment. Moreover, an average loading of ∼11 fg iron/cell caused by magnetic labelling was determined in magnetic particle spectroscopy. Importantly, hemodynamic measurements as well as histological examinations using a myocardial ischemia/reperfusion mouse model showed no influence of MACS ® MicroBeads on cardiac regeneration, while the transplantation of stem cells caused a significant improvement. Furthermore, immunostainings demonstrated the clearance of co-injected iron nanoparticles from stem cells and the surrounding heart tissue within 48 h post transplantation. Conclusions: Our results indicate that iron amounts typically co-injected with MACS ® purified stem cells do not harm cardiac functions and are cleared from heart tissue within a few hours. Therefore, we conclude that MACS ® MicroBeads exhibit a good compatibility in the cardiac environment.